Re-thinking Populism within the Borders of Democracy - Gerim, Giray (Italian Sociological Review, 2018)
Although populism has many references and various definitions as an elusive and ambiguous concept, this article approaches it as a political project which has a potential to undermine democracy in some ways. This approach enables a broader comprehension of populism rather than confining it to some ideological tenets or a few undisputed populist movements. In the study, it is attempted to reveal the logic of this political project through a tripartite analysis which consists of the sense of democracy inherent in populism, its way of thinking and reasoning, and the political circumstances which enables and strengthens populism. It is argued that the analysis performed here can offer an outline of the ground on which the struggle against the features of populism, that threatens democracy, can be carried out. Finally, in the light of the aforementioned analysis and some ideas which are borrowed from the works of Habermas and Mouffe to a large extent and discussed in an interconnected manner, it is aimed to re-read democracy as an answer to problems arising out of populism.